THE APPLICATION OF IMLA' METHOD TO THE ARABIC LANGUAGE WRITING ABILITY OF MA AS'ADIYAH MAKASSAR STUDENTS (Karya Ilmiah Mahasiswa (KIMA), 2023)
This research was conducted at MA As'adiyah Makassar aims at finding  out the process of applying the Imla’ method and its difficulties on the ability to write Arabic in class XI MA As'adiyah Makassar students This research was a simple qualitative and quantitative descriptive analysis research. Data were collected by observation, interview, documentation and questionnaire methods. The collected data was analyzed by means of reduction, presentation of data and verification or drawing conclusions. The results showed, (1) the application of the imla' method to the writing skills of class XI MA As'adiyah Makassar students, a) before learning, the teacher explained hijaiyah letters that could be connected and not connected; b) the implementation of the imla' that is carried out was imla' masmu'; c) after imla’, the teacher corrects and shows the correct writing; d) the responses given by students regarding learning using the imla' method in class showed that there was an effect of the imla' method on improving students' Arabic writing skills. (2) The difficulty of applying the imla’ method to students' writing ability a) the lack of allotted learning time given during class learning; b) lack of student attention during the learning process; c) lack of student interest in learning; d) students are not yet able to write Arabic with connected letters; e) students have not been able to distinguish the pronunciation of hijaiyah letters that are similar; f) students are still lacking in listening to Arabic reading properly.